Approach regions for $l^{p}$ potentials with respect to the square root of the Poisson kernel - Brundin, Martin (MATHEMATICA SCANDINAVICA, 2005)
If one replaces the Poisson kernel of the unit disc by its square root, then normalised Poisson integrals of $L^{p}$ boundary functions converge along approach regions wider than the ordinary nontangential cones, as proved by Rönning ($1≤ p<∞$) and Sjögren ($p=1$ and $p=∞$). In this paper we present new and simplified proofs of these results. We also generalise the $L^{∞}$ result to higher dimensions.